Power efficient dual‐dependent pilots' channel estimation for filter bank multi‐carrier with offset quadrature amplitude modulation. Issue 4 (1st March 2019) - Yu, Xiang; Li, Yangyang; Duan, Sirui
Abstract : The channel estimation for a filter bank multi‐carrier with offset quadrature amplitude modulation has been considered an attractive scheme alternative to the conventional cyclic prefix (CP)‐orthogonal frequency‐division multiplexing. However, all the advantages come at the price of the real‐field orthogonality conditions, which gives rise to the intrinsic imaginary. Especially the channel estimation algorithm with a scattered‐pilot structure, which neutralises the interference by increasing power or reducing spectrum efficiency to get accurate channel estimation coefficients. In this work, dual‐dependent pilot (DDP) channel estimation algorithm is studied. By analysing the interference at the pilot position and pilot power, the authors propose an improved power efficient scattered DDP channel estimation method. The proposed method regards the interference as a part of the pilot rather than cancelling it. Moreover, in order to fully utilise intrinsic interference, phase ambiguity is introduced into predefined pilots to adapt to different intrinsic interference values, combined with the reference pilot and DFT iteration to solve phase ambiguity problems at the receiver. Theoretical analysis shows that the improved method can effectively improve the power efficiency. Furthermore, numerical results show the validity of the theoretical analysis and the reliability of the new method.